PENGARUH RELIGIUS SEKOLAH TERHADAP KEBERAGAMAAN SISWA (Studi Komparatif di MIN Pematang Bangau dan SDIT Alqalam Kecamatan Kota Manna Kabupaten Bengkulu Selatan) - Aslianah Aslianah (UIN Fatmawati Sukarno Bengkulu, 2017)
Religious school has a uniqueness that is religiously implemented in schools both public and swasta.Namun fact, the Islamic primary school have integrated Alqalam more parents to send their children than the State Government Elementary School bund Stork though the cost to be paid much more expensive. This study was conducted to address three issues: (1) whether there is an applied religious differences; (2) whether there are differences in the level of diversity of their students; and (3) whether there is any religious influence of the religious school students Pematang Stork State Islamic Elementary School and Elementary School Isam Alqalam Sub City Manna South Bengkulu. This research is an explanatory research.Sampel taken as many as 120 people from 190 populasi.Data collected using questionnaires and observation. Data were analyzed using different test average and simple linear regression. The results showed that: (1) religious in Pematang Stork State Government Elementary School and Elementary School Isam Alqalam Manna City District of South Bengkulu has been well implemented, and there is no difference in the values and teachings are applied to both schools. The difference lies in the way / techniques used to internalize value. (2) The level of diversity of elementary school students Isam Alqalam higher than the State Government Elementary School students Causeway Stork, however, both in the high category. Islamic elementary school students integrated Alqalam higher than Pemadang Stork State Islamic Elementary School in peace indicators, while the State Islamic Elementary School students Causeway Stork higher than Alqalam Integrated Islamic Elementary School in the indicator gratitude. (3) Culture religious school (X) has positive influence on the religious students(Y) in the State Government Elementary School Primary School Pematang Stork and Isam Alqalam Sub City Manna South Bengkulu. The linear regression equation generated from research is Y = 57.858 + 0,360X. This means that the better implementation of religious school, the higher the level of religious students.